Science or popular media: What drives breast cancer online activity?. Issue 2 (26th July 2017) - Sugrue, Ryan; Carthy, Erica; Kelly, M. E.; Sweeney, Karl J.
Abstract: Google Trends is reflective of international awareness. Since its launch in 2004, there have been several landmark publications, international awareness campaigns, and mainstream‐media events that involve breast cancer. The aim of this study was to assess the impact of landmark academic publications vs mainstream‐media announcements in driving online breast cancer activity via Google Trends. Ten breast cancer‐related themes or landmark publications (five academic publications and five media‐related events) were used to compare the impact of online search activity. This activity was determined by retrospectively analyzing Google Trends data over a 12‐year period (2004‐2016) and calculating the relative search volume. Breast cancer searches showed a slight decrease in the twelve‐year period. Since 2004, eight of top 10 Breast Cancer searches were in October. This coincides with breast cancer awareness month. The major five academic publications were all published in the New England Journal of Medicine or the Lancet. Interestingly, only one publication (Tailor‐X trial) made the top 10 spikes in relative search volume. Academic publications as expected generate lower rates of public awareness and Internet searching. However, if academic publications are coupled with media releases, there is considerable potential for achieving increased public awareness.